Design Challenges of Interactive Spherical User Interfaces - Benko, Hrvoje; Wilson, Andy (Programming Reality Workshop at CHI'09, 2009)
We present our experience on designing interactive applications for Sphere, our multi-touch-sensitive spherical display prototype. We believe that the compelling application design for future non-flat user interfaces will greatly depend on exploiting some unique characteristics of the given form factor. While our observations primarily focus on spherical displays, we envision that the ideas presented here are applicable to a variety of non-flat or curved display form factors that will be available in the future.